Development and quality evaluation of polyphenols enriched black carrot (Daucus carota L.) powder incorporated bread - Pragya Pandey; Kiran Grover; Tarsem Singh Dhillon; Neena Chawla; Amarjeet Kaur (Heliyon, 2024)
Black carrot is a prominent source of polyphenols and the cheapest source of anthocyanins in India. In this study, an attempt has been made to examine the feasibility of black carrot powder as an ingredient in bread. Black carrot bread was prepared by incorporating different concentrations of black carrot powder (BCP) at 2.5, 5.0, 7.5 and 10 %. The developed bread samples were analyzed for physical and textural quality, proximate composition, bioactive compounds, antioxidant properties, sensory characteristics, mineral content and storage quality. The results revealed that loaf volume and specific volume decreased (1995–1254 mL, 5.25–3.28 mL/g) with the incorporation of BCP into bread. Textural analysis revealed that the addition of BCP led to increased hardness in the bread (0.110–12 0.151 N), whereas the resilience (43.64–35.10 %), cohesion and springiness (89.930–13 82.146 %) decreased significantly. The content of bioactive compounds such as total phenols, anthocyanins (29.63–112.68 mg/100 g) and flavonoids increased to exceptionally high levels in BCP-incorporated bread and showed high antioxidant activity. Incorporation of BCP up to 7.5 % showed the most acceptable sensory analysis score (7.85) with a significant increase in dietary fiber (40 %) and total mineral content (50 %), which revealed that black carrot powder could be used up to 7.5 % as an ingredient into bread with high acceptability. The present study revealed significant enhancement in bioactive compounds and mineral content of bread after the incorporation of black carrot powder, which supports its immense potential in preventing hunger and oxidative stress-induced disorders in developing countries.